Casos de Ensino no Brasil: Análise Bibliométrica e Orientações para Autores - Marina Faria; Kleber Fossati Figueiredo (RAC: Revista de Administração Contemporânea, 2013)
The demand for the use of active teaching methods is increasing in management courses. Correspondently, a growing number of teachers are using the case method. In order to encourage the spread of cases in Brazil, the Associação Nacional de Pós-Graduação e Pesquisa em Administração (ANPAD - Brazilian Academy of Management) began accepting teaching cases in its conferences in 2007. This research aims to propose guidelines for Brazilian scholars who wish to produce teaching cases based upon a panorama of national cases published between 2007 and 2011. We performed a bibliometric analysis of publications in ANPAD sponsored events and major national journals. The most common problems related to teaching notes. The majority of cases are indicated by the authors as useful in the areas of strategy and marketing, but there are areas with few cases, such as people management, logistics and finance. Our analysis drew attention to the predominance of a player profile and lack of diversification in data sources used for case preparation. This article provides 16 guidelines for Brazilian scholars who wish to producing teaching cases in management.